Effects of alendronate and interferon-γ on bone cancer cells in vitro. Issue 1 (1st January 2018) - Barone, Andrew W.; Fernandes, Gabriela; Dziak, Rosemary
Abstract: Bisphosphonates are used to reduce pathological osteolysis in bone cancer patients. In addition to direct effects on tumor cells, these drugs may also alter the production of immune cell factors within the tumor microenvironment. Interferon-γ (IFN-γ) represents one such factor whose production by T lymphocytes is increased following bisphosphonate treatment. This study characterized the effects of alendronate (ALN), an aminobisphosphonate, and IFN-γ on viability, maturation, and osteoclastic factor production in human G292 osteosarcoma cells. Viability was assessed with a colorimetric assay; maturation by alkaline phosphatase (ALP) and mineralization via alizarin red. Receptor activator of nuclear factor kappa-Β ligand (RANKL) and monocyte chemoattractant protein-1 (MCP-1) production were quantified with ELISAs. ALN (5 nM) had no effect on viability. IFN-γ (1, 000 U/mL) decreased this parameter alone and in the presence of ALN. ALN had a transient inhibitory effect on ALP. While IFN-γ increased this parameter, ALN inhibited this effect. Whereas ALN and IFN-γ each decreased RANKL, cotreatment with IFN-γ lessened the inhibitory effect of ALN. ALN decreased MCP-1 and attenuated IFN-γ induced increases. These studies suggest that bisphosphonates have direct effects on bone tumor cells and on the actions of cytokines in the tumor microenvironment and provide a basis for optimization of bone cancer therapy.